Introduction to random division multiple access (RDMA) applicable for mobile satellite communications - Stojce Ilcev, Dimov (International Journal of Engineering and Technology, 2019)
This paper describes in particular Random Division Multiple Access (RDMA) applicable in Mobile Satellite Communications (MSC). In satellite communication systems, as a rule, especially in Mobile Satellite Communications (MSC) many users are active at the same time. The problem of simultaneous communications between many single or multipoint mobile satellite users, however, can be solved by using Multiple Access (MA) technique. Since the resources of the systems such as the transmitting power and the bandwidth are limited, it is advisable to use the channels with complete charge and to create a different MA to the channel. This generates a problem of summation and separation of signals in the transmission and reception parts, respectively. Deciding this problem consists in the development of orthogonal channels of transmission in order to divide signals from various users unambiguously on the reception part.
Keywords: FDMA; TDMA; CDMA; RDMA; MSC; MA; Aloha; Slotted Aloha; Slot Reservation Aloha.